The new digital conglomerates - Herrero Suárez, Carmen (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The formation of large ecosystems and digital platforms has reopened a debate on the effects that may arise on competition from mergers of a conglomeral nature, recovering old concerns and raising new fears about the anti-competitive potential of these business restructuring operations.
Keywords: Mergers; conglomerates; structure; innovation